Development of a technology-integrated ethnomathematics digital comic using hadroh music context: effects on students’ numeracy and self-regulated learning - Kartika Rusiyaningsih; Gunawan Gunawan (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Mathematics plays a vital role in fostering logical, analytical, and systematic thinking in the 21st century, with numeracy and self-regulated learning recognized as essential competencies in the Merdeka Curriculum. However, students’ numeracy skills and learning independence remain relatively low, particularly among Grade VIII students at SMP Negeri 1 Pekuncen. Aims: This study aims to develop a technology-integrated ethnomathematics digital comic using a hadroh music context and to evaluate its validity, practicality, and effectiveness in improving students’ numeracy skills and self-regulated learning. Method: This research employed a Research and Development (R&D) approach based on the 4D model (Define, Design, Develop, Disseminate). The study involved Grade VIII students in the 2025/2026 academic year. Data were collected through expert validation sheets, questionnaires, and numeracy tests, and analyzed using both descriptive and inferential statistical techniques. Results: The developed digital comic was categorized as valid, with material expert validation of 77.7% and media expert validation of 84%. It was also considered practical based on positive responses from teachers and students. Descriptive findings indicate improved numeracy scores and self-regulated learning in the experimental group. Inferential analysis shows that self-regulated learning improved significantly, while numeracy improvement demonstrated a positive but not statistically significant trend. Conclusion: The ethnomathematics-based digital comic integrating hadroh music is valid, practical, and has strong potential to enhance students’ learning autonomy and contextual mathematical understanding.